2008
DOI: 10.1111/j.1468-1331.2008.02119.x
|View full text |Cite
|
Sign up to set email alerts
|

Correlation between sleep and cognitive functions after hemispheric ischaemic stroke

Abstract: Background:  The aim of this study was to test the hypothesis of a link between sleep and cognitive functions, particularly memory and attention, after stroke. Methods:  We studied 11 consecutive patients with first‐ever hemispheric ischaemic stroke within eight days after symptoms onset and nine of them at least three months after stroke. Sleep EEG was recorded with a portable system. Cognitive functions were assessed using a standardized battery of tests allowing the estimation of the most relevant domains o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
42
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 34 publications
1
42
0
1
Order By: Relevance
“…In their study, Schuiling et al (2005) found that sleep fragmentation was one of the most frequent findings in patients with hemorrhagic stroke. Siccoli et al (2008) analyzed continuous night waking and reported longer wake duration during sleep time in the acute stage when compared to the subacute and chronic stages of the disease. Seitz et al (2011) found that some patients in the acute stage after middle cerebral artery stroke show a secondary decline in general motor activity related to an enhanced sleep demand.…”
Section: Discussionmentioning
confidence: 98%
“…In their study, Schuiling et al (2005) found that sleep fragmentation was one of the most frequent findings in patients with hemorrhagic stroke. Siccoli et al (2008) analyzed continuous night waking and reported longer wake duration during sleep time in the acute stage when compared to the subacute and chronic stages of the disease. Seitz et al (2011) found that some patients in the acute stage after middle cerebral artery stroke show a secondary decline in general motor activity related to an enhanced sleep demand.…”
Section: Discussionmentioning
confidence: 98%
“…These results suggest that this increase of non-REM sleep at 2 days is not related to SD intervention but rather to an effect of the SD as the preconditioning effect that should be clarified in the future. Indeed, there are studies at supporting the fact that non-REM sleep is a good predictor of favourable outcomes after hemispheric ischemia [17, 18]. …”
Section: Discussionmentioning
confidence: 99%
“…De acordo com a literatura, pacientes com um único evento isquê-mico mostraram uma correlação entre o desempenho da memória verbal e não verbal com a quantidade de sono de ondas lentas, sono REM e eficiência do sono, sugerindo uma ligação entre o sono e as funções cognitivas após o AVE 14,15 . Assim, a investigação de problemas relacionados ao sono é um importante componente da abordagem diagnóstica e terapêutica clínica.…”
Section: Discussionunclassified